PENGARUH STRUKTUR AUDIT, TEKANAN WAKTU, DISIPLIN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR - I Ketut Eka Putra; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2021)
The purpose of this research is toexamine The Effect of Audit Structure, Time pressure, Work discipline and Organization commitment toward Auditor Performance at Public Accountant Office in Denpasar. This research conducted to auditor who work at 16 (sixteen) Public Accountant Office that own in Bali with 120 auditors. Data accumulation method used questioner and analyzed using Double Regression Analysis. Based on the result of distributing 120 questioners, the researcher found that audit Structure, work discipline and organization commitment have positive and significant impact to auditor performance. Meanwhile time pressure does not impact to variabel auditor performance. If the organization side wish to maximalist auditor performance therefore better to observe back to some factors that exist in audit structure, work discipline, and organization commitment